Effect of Feeding Rate on Growth Performance and Waste Reduction Efficiency of Black Soldier Fly Larvae (Diptera: Stratiomyidae) - Moo Chee Yuan,; Hadura Abu Hasan, (Tropical Life Sciences Research, 2022)
Malaysia like many other developing countries is facing the challenge of poor waste management. This research was conducted to determine the effect of black soldier fly (BSF) larvae in decomposing food waste, palm oil waste, fish waste and yard waste. The development time and waste reduction efficiency of four different organic materials were evaluated. In this study, BSF larvae were fed with all four types of waste at five feeding rates of 0.25, 0.50, 1.00, 1.50 and 2.00 g larva?1 day?1 with three replicates per feeding rate until the larvae reached the pre-pupae stage. During the study, larval development time, larval mortality, pre-pupae weight and waste reduction indexes (WRI) were determined. Food waste and yard waste achieved the highest WRI of 4.43 ± 0.06 and 0.71 ± 0.01, respectively at the feeding rate of 0.50 g larva?1 day?1 while palm oil waste and fish waste attained the highest WRI values at feeding rates of 1.00 g larva?1 day?1 (1.89 ± 0.02) and 0.25 g larva?1 day?1 (3.75 ± 0.24), respectively. The results showed that both variables significantly influenced the bioconversion process, but waste reduction efficiency was the most influential element. Malaysia seperti kebanyakan negara membangun yang lain menghadapi cabaran pengurusan sampah yang kurang baik. Penyelidikan ini dilakukan untuk mengetahui kesan larva lalat askar hitam dalam menguraikan sisa makanan, sisa kelapa sawit, sisa ikan dan sisa halaman. Masa perkembangan dan kecekapan pengurangan sisa empat bahan organik telah dinilai. Dalam kajian ini, larva lalat askar hitam diberi makan dengan empat jenis sisa pada lima kadar pemakanan iaitu 0.25, 0.50, 1.00, 1.50 dan 2.00 g larva?1 hari?1 dengan tiga ulangan setiap kadar pemakanan sehingga larva mencapai peringkat pra-pupa. Semasa kajian, masa perkembangan larva, kematian larva, berat badan pra-pupa dan indeks pengurangan sisa ditentukan. Sisa makanan dan sisa halaman mencapai indeks pengurangan sisa tertinggi iaitu 4.43 ± 0.06 dan 0.71 ± 0.01, masing-masing pada kadar makan 0.50 g larva?1 hari?1 sementara sisa kelapa sawit dan sisa ikan mencapai nilai indeks pengurangan sisa tertinggi pada kadar pemakanan 1.00 g larva?1 hari?1 (1.89 ± 0.02) dan 0.25 g larva?1 hari?1 (3.75 ± 0.24), masing-masing. Hasil kajian menunjukkan bahawa kedua-dua pemboleh ubah mempengaruhi proses bio-penukaran secara signifikan, tetapi kecekapan pengurangan sisa merupakan elemen yang paling berpengaruh.